A Study of Hopf and Amplitude-Controlled Phase Oscillators for Snake Robot Locomotion - Karaçöl, Serkan; Korkmaz, Deniz; Koca, Gonca Ozmen; Karabulut, Narin (My University, 2019)
In this paper, we propose a motion control which can produce rhythmic movements of a snake-like robot by using Center Pattern Generator. The snake robot is designed in SolidWorks environment and composed of a head, a propulsion mechanism and a tail connected the last link. The designed model is also adapted to Matlab/SimMechanics environment in order to observe the motion of the robot and analyze the constructed Central Pattern Generator networks. Central Pattern Generator based networks are carried out with Amplitude-Controlled Phase and Hopf oscillators to create rhythmic, stable, oscillatory and robust locomotion patterns. The both network structures are constructed with bidirectional chain models. In order to analyze the locomotion of the snake-like robot, S-type forward and C-type turning motions are performed. The simulation results show that the Amplitude-Controlled Phase oscillator with bidirectional chain network structure gives effective, smooth and robust control performance for both forward and turning motions of the snake robot. Thus, a base of more intelligent locomotion control approach with Amplitude-Controlled Phase oscillator is provided and some critical comparisons are performed.
Keywords: Robotik; Bilgisayar Bilimleri; Yapay Zeka